Synthesis of 3-Formylbenzenesulfonyl Chloride Derivatives - Bao, Xuefei; Liu, Ziao; Liang, Xinjie; Song, Dake; Shi, Tao; Zhao, Xuan; Bao, Changshun; Chen, Guoliang (Synthesis, 2017)
A synthetic route to 3-formylbenzenesulfonyl chloride derivatives from the corresponding benzaldehydes has been developed. The key step in this procedure is the conversion of aldehyde bisulfite adducts to target compounds via a two-stage reaction in the presence of Na2SO4. A series of 3-formylbenzenesulfonyl chloride derivatives were prepared by this method and identified by chemical derivatization method.
Keywords: 3-formylbenzenesulfonyl chloride; aldehyde sodium bisulfite; chlorosulfonation; two-stage reaction; chemical derivatization method